2004
DOI: 10.1161/01.cir.0000127959.28627.f8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Obesity and Insulin Resistance on Myocardial Substrate Metabolism and Efficiency in Young Women

Abstract: Background-Obesity is a risk factor for impaired cardiac performance, particularly in women. Animal studies suggest that alterations in myocardial fatty acid metabolism and efficiency in obesity can cause decreased cardiac performance.In the present study, we tested the hypothesis that myocardial fatty acid metabolism and efficiency are abnormal in obese women. (rϭ0.58, PϽ0.005). A multivariate, stepwise regression analysis showed that BMI was the only independent predictor of MV O 2 and efficiency (Pϭ0.0005 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
423
7
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 574 publications
(472 citation statements)
references
References 40 publications
31
423
7
7
Order By: Relevance
“…In a study of young women with uncomplicated obesity, our group found that myocardial FA upake, utilization, and oxidation all were increased as BMI and whole body insulin resistance increased, paralleling what was found in animal models of obesity [56,58]. It appears that this increased FA oxidation capacity in humans may also be overwhelmed, as it can be in animal models because autopsy and magnetic resonance spectroscopy studies both demonstrate that in subjects with diabetes there is an increase in intramyocellular triglyceride compared with normal controls [59].…”
Section: Obesity and Myocardial Metabolismsupporting
confidence: 59%
See 1 more Smart Citation
“…In a study of young women with uncomplicated obesity, our group found that myocardial FA upake, utilization, and oxidation all were increased as BMI and whole body insulin resistance increased, paralleling what was found in animal models of obesity [56,58]. It appears that this increased FA oxidation capacity in humans may also be overwhelmed, as it can be in animal models because autopsy and magnetic resonance spectroscopy studies both demonstrate that in subjects with diabetes there is an increase in intramyocellular triglyceride compared with normal controls [59].…”
Section: Obesity and Myocardial Metabolismsupporting
confidence: 59%
“…Lastly, increasing BMI is an independent predictor of increasing myocardial oxygen consumption and decreasing efficiency both in animal models and in a recent study in young obese women [58,66]. Decreased efficiency may contribute to impaired ATP production, thereby hindering cardiac function, and decreased efficiency is a hallmark of heart failure.…”
Section: Obesity and Myocardial Metabolismmentioning
confidence: 89%
“…5,6 Some recent observations by positron emission tomography showed that in obese young women, insulin resistance and obesity are strictly related to alterations of fatty acid metabolism (uptake, utilization and oxidation), which could play a role in a decreased cardiac performance. 7 Indeed, long-standing obesity can induce left ventricular structural and functional abnormalities, characterized by volume overload and hyperdynamism, eccentric left ventricular hypertrophy, diastolic dysfunction and, occasionally, systolic dysfunction and heart failure. 8 Pulsed-Wave Tissue Doppler Imaging (PW-TDI) of the mitral annulus has demonstrated the capability to a relatively load-independent analysis of the global longitudinal myocardial 9,10 Color-Doppler Myocardial Imaging (CDMI) echocardiography-derived strain rate (SR) and strain measurements are new quantitative indices of regional intrinsic myocardial deformation.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in MVO 2 associated with an increase in BMI is likely related to the effect of obesity on cardiac remodeling and the fact that obesity increases sympathetic tone, preload and fatty acid metabolism. Increased fatty acid uptake and oxidation by the heart can also increase MVO 2 , because more oxygen is required to generate ATP from fatty acid than by glucose metabolism 5 . In agreement with our study, Linda R. Peterson et al demonstrated in young women, obesity is a sign ificant predictor of increased MVO 2 and decreased cardiac efficiency 5 .…”
Section: Discussionmentioning
confidence: 99%
“…But the data from animal studies suggest that obesity increases myocardial fatty acid metabolism & oxygen consumption leading to increased oxidative stress, cardiac dysfunction & apoptosis 5 . We limited our study population to women because obesity is more common in women than in men and the relative risk of heart failure is greater in obese women than in obese men 5 . Women gain weights mostly between ages of 35 -45 yrs of age.…”
Section: Introductionmentioning
confidence: 99%